Effect of Chromium Interlayer Thickness on Optical Properties of Au-Ag Nanoparticle Array. (19th August 2014) - Liu, Jing; Cai, Haoyuan; Kong, Lingqi; Zhu, Xianfang
Abstract : The effect of chromium interlayer thickness on optical properties of array of hybrid Au-Ag triangular nanoparticles is systematically investigated. The optical spectrum simulated by discrete dipole approximation (DDA) numerical method shows that with increase of the chromium interlayer thickness both refractive index sensitivity (RIS) and figure of merit (FOM) of localized surface plasmon resonance from the hybrid nanostructures experience remarkable change and the intensity of the extinction efficiency decreases. The nanosphere lithography (NSL) is used to fabricate the hybrid nanostructure arrays with different chromium interlayer thicknesses. The experiment demonstrates that the spectrum as measured from the as-fabricated hybrid nanostructure arrays is essentially in agreement with the simulated results.